2000
DOI: 10.1103/physrevlett.84.3314
|View full text |Cite|
|
Sign up to set email alerts
|

Patterning Electro-osmotic Flow with Patterned Surface Charge

Abstract: This Letter reports the measurement of electro-osmotic flows (EOF ) in microchannels with surface charge patterned on the 200 mm scale. We have investigated two classes of patterns: (1) Those in which the surface charge varies along a direction perpendicular to the electric field used to drive the EOF; this type of pattern generates multidirectional flow along the direction of the field. (2) Those in which the surface charge pattern varies parallel to the field; this pattern generates recirculating cellular fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
225
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(234 citation statements)
references
References 12 publications
9
225
0
Order By: Relevance
“…Anderson & Idol (1985) explored electro-osmotic flow in inhomogeneously-charged pores, and found eddies and recirculation regions. Ajdari (1995;2001) and Stroock et al (2000) showed that a net electro-osmotic flow could be driven either parallel or perpendicular to an applied field by modulating the surface and charge density of a microchannel, and Gitlin et al (2003) have implemented these ideas to make a 'transverse electrokinetic pump'. Such transverse pumps have the advantage that a strong field can be established with a low voltage applied across a narrow channel.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson & Idol (1985) explored electro-osmotic flow in inhomogeneously-charged pores, and found eddies and recirculation regions. Ajdari (1995;2001) and Stroock et al (2000) showed that a net electro-osmotic flow could be driven either parallel or perpendicular to an applied field by modulating the surface and charge density of a microchannel, and Gitlin et al (2003) have implemented these ideas to make a 'transverse electrokinetic pump'. Such transverse pumps have the advantage that a strong field can be established with a low voltage applied across a narrow channel.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques have been proposed to locally generate various charge patterns. Laminar flow patterning was used to generate longitudinal patterns, while a modified version of micromolding in capillaries was used to create transverse patterns [13]. In another approach, polymer coating by an electrostatic-self-assembly (ESA) combined with standard photolithography was used to generate several different surface charge patterns [14].…”
Section: Introductionmentioning
confidence: 99%
“…Results from the three-dimensional model were verified against the well-known classical results for homogeneous surfaces 34,35 as well as the one-dimensional experimental results presented by Herr et al 27 In addition, the BLOCS code used in this study has been checked against several classical flow test problems, such as flow over a backward step and flow in a square cavity, and experimentally verified in previous works. 36 Of immediate interest here would be a qualitative comparison with the two-dimensional results of Ajdari 20 and Stroock et al 25 using the lengthwise and crosswise strip patterns as shown in Figure 1a,b (note that Ajdari actually considered a sinusoidally varying surface charge density as opposed to the step changes examined here; however, as will be shown, a similar flow structure exists). To do this, we consider a computational domain with dimensions l x ) 50 µm, l y ) l z ) 25 µm (the x-y-z coordinate system is as shown in Figure 2) containing a 1 × 10 -5 M KCl solution (thus a double-layer thickness, 1/κ, of 0.1 µm) and an applied driving voltage of 500 V/cm.…”
Section: Comparison With Previously Published Resultsmentioning
confidence: 99%
“…The results for the lengthwise strips are shown in Figure 3 and Figure 4 for the crosswise strips. 25 the flow is directed along the negative x-axis over the heterogeneous strips and the positive x-axis over the homogeneous patch, in both cases becoming weaker and approaching zero near the transition point. Also of interest is the change in the magnitude of the induced flow velocity with increasing distance from the surface.…”
Section: Comparison With Previously Published Resultsmentioning
confidence: 99%
See 1 more Smart Citation